2010
DOI: 10.4081/rt.2010.e54
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-associated lymphoid tissue lymphoma and concurrent adenocarcinoma of the prostate

Abstract: Primary mucosa-associated lymphoid tissue (MALT) lymphoma of the prostate is a rare disease that characteristically follows an indolent course. It is believed that infection or chronic inflammation may be triggers for malignant transformation in the prostate, but it is of unknown etiology. Reports of MALT lymphomas of the prostate with other concurrent primary prostate cancers are even more limited. We present the unique case of a 67-year-old male with concurrent adenocarcinoma of the prostate and primary MALT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Lymphomas of prostate, either primary or secondary, are very rare. The types are mainly consisted of B-cell lymphomas [6], including diffuse large B-cell non-Hodgkin’s lymphoma (DLBL) [7], mucosa-associated lymphoid tissue (MALT) lymphoma [8], and mantle cell lymphomas [9]. Only three cases of T-cell lymphomas involving the prostate have been reported, but none of them was primary [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphomas of prostate, either primary or secondary, are very rare. The types are mainly consisted of B-cell lymphomas [6], including diffuse large B-cell non-Hodgkin’s lymphoma (DLBL) [7], mucosa-associated lymphoid tissue (MALT) lymphoma [8], and mantle cell lymphomas [9]. Only three cases of T-cell lymphomas involving the prostate have been reported, but none of them was primary [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…3 The common clinical symptoms and signs include dysuria, urine frequency and urgency, anal pendant expansion, and difficult bowel movement. 4 The present case involved an 81-year-old male patient with a histopathologic diagnosis of prostate large B-cell malignant lymphoma. Some other studies reported that DRE often revealed prostate hyperplasia, hard consistency and disappearance of the central fissure, or nodules in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphom-ahnliche Lasionen (LLL) sind auch in der Vulva berichtet warden und es ist schwierig, diese von Lymphomen zu unterscheiden (s. Zervix) [149,255]. 101,103,115,131,160,192,229]. AuGerdem wurde eine blastare Transformation zu einem DLBCL bei MALT-Lymphomen der Prostata berichtet [192].…”
Section: Vulvaunclassified